The Correlation Between Self-Care and Family Support With The Quality of Life of Type II Diabetic Mellitus Patient in Public Health Center I of West Denpasar - Anggreni, Ni Kadek Dwi Yanti; Manangkot, Meril Valentine; Pramitaresthi, I Gusti Ayu (Journal of A Sustainable Global South; Vol 5 No 2 (2021): August 2021, 2021)
Diabetes mellitus (DM) is a metabolic disease with characteristics of hyperglycemia. Type 2 DM that is not handled properly will result in complications that affect the quality of life. Type 2 DM patients need to do self-care as one of the DM treatment. In addition to self-care, the quality of life of DM patients is also related to family support. This study aims to determine the relationship between variables of self-care and family support with the quality of life of patients with type 2 DM. The study was conducted on 26 March-23 April 2019. This study was a quantitative study with a cross sectional approach. The number of the respondents were 59 people, obtained through consecutive sampling technique. Self-care was measured using a summary of diabetes self-care activity (SDSCA) questionnaire, family support was measured using the diabetes family behavior checklist II (DFBC II) questionnaire, and quality of life was measured using the diabetes quality of life (DQOL) questionnaire. The data analysis was done using Pearson Product Moment test. The results showed that there was a relation between self-care and quality of life (p = 0.000, r = 0.548) and there was a relation between family support and quality of life (p = 0.005, r = 0.365). Health workers are expected to develop health education which is not only needed for type 2 DM patients but also their families in order to realize optimal quality of life. Index Terms — family support, quality of life, self-care, type 2 DM